Microsporum spp as a cause of dermatophytosis: a review (Research, Society and Development, 2020)
Dermatophytoses are superficial infections that are characterized by the involvement of skin, hair and nails, presenting fungi of the genus Microsporum as important causes of these diseases. Thus, the present study aimed to conduct a literature review on the genus Microsporum, highlighting the possible dermatophytoses that species of this genus can cause, as well as epidemiological, pathogenic, immunological characteristics, the diagnosis and the pharmacological treatment currently employed. M.canis and M.gypseum has been presented as the main species of the genus Microsporum from a clinical-epidemiological point of view, with a predominance of dermatophytoses associated with M. canis. It is observed that fungi of this genus mainly cause tinea capitis and tinea corporis, so that the diagnosis can be of the clinical type, through the analysis of the lesions and, above all, laboratory through microscopy using potassium hydroxide (KOH) for the elucidation of fungal structures. For the infection to occur, the acidity of the skin becomes important, in addition, the immune response has been associated with Toll Like Receptors. Pharmacological treatment can be done with allylamines, azoles or griseofulvin, in which resistance phenomena have already been associated with these drugs. Thus, the data present in this research can guide other studies that focus on fungi of the genus Microsporum.